Use of flow cytometry to quantify intracellular Leishmania sp. - Silva, Adriana Carneiro da (2022)
The search for new methodologies that make the work in the search for new drugs more precise, agile, and with greater standardization is very important to the study of leishmaniasis. The technique most used to assess the leishmanicidal effect of a given drug in vitro, the slide count, despite being consolidated in the scientific environment, presents several difficulties in its execution, assessment, and results. In addition to being laborious, this technique takes time, both for the preparation of the material for analysis and for the counting itself. Based on this need, our research group proposes a new methodology based on nuclear labeling, using propidium iodide and flow cytometry to quantify the parasite load of Leishmania sp. in macrophages in vitro. Our results show that the fluorescence of infected samples increases as the infection rate increases. Using Pearson's Correlation analysis, it was possible to establish a correlation coefficient (Pearson r = 0.9473) that was positive, linear, and directly proportional to the variables fluorescence and infection rate. Thus, it is possible to infer a mathematical equation, through linear regression, to obtain an estimate of the number of parasites in each sample through the Relative Fluorescence Units (RFU) values. This new methodology opens space for the possibility of using this methodological resource in the in vitro quantification of Leishmania sp. in macrophages. Keywords: Flow cytometry. Leishmaniasis. Propidium iodide.